PEDAGOGICAL ACTIVITY OF MIRZO ULUG'BEK (World Bulletin of Social Sciences, 2024)
This article provides detailed information about Mirzo Ulugbek's life and activities, state administration, contribution to science, and pedagogical activities.
Keywords: History of Arba ulus; observatory; madrasa; academy